Updates on the genus Euphorbia (Euphorbiaceae) in Santa Catarina, Brazil - Hassemer, Gustavo; Da Silva, Otávio Luis Marques; Funez, Luís Adriano; Ernst, Madeleine; Cordeiro, Inês; Rønsted, Nina (Phytotaxa, 2017)
This contribution presents updates to the knowledge of the species of Euphorbia that occur in Santa Catarina state, southern Brazil. More specifically, we here typify the names E. cyathophora, E. hirtella, E. paranensis and E. stenophylla, and present the first records of E. cyathophora, E. graminea, E. ophthalmica and E. thymifolia for Santa Catarina. Finally, we provide an updated identification key to all 30 species of Euphorbia that occur in Santa Catarina, including native, naturalised and cultivated species.